2020
DOI: 10.3390/nu12123842
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Nutritional Issues Associated with Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA), the main genetic cause of infant death, is a neurodegenerative disease characterized by the selective loss of motor neurons in the anterior horn of the spinal cord, accompanied by muscle wasting. Pathomechanically, SMA is caused by low levels of the survival motor neuron protein (SMN) resulting from the loss of the SMN1 gene. However, emerging research extends the pathogenic effect of SMN deficiency beyond motor neurons. A variety of metabolic abnormalities, especially altered fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 86 publications
2
46
0
Order By: Relevance
“…Low-fat diets with high sucrose content had the best effect in normalizing abnormal readouts (such as ketones), suggesting that this led to lesser reliance on fat as an energy source [ 41 ]. However, some discordant studies exist and have been discussed more extensively elsewhere [ 41 , 62 , 257 ]. An early small study looking at a low-fat/high carbohydrate diet claimed positive results [ 92 ], but concerns about its validity remain as this was ahead of genetic testing and the classification of patients was unclear.…”
Section: Nutritional Guidelines For Sma Patientsmentioning
confidence: 99%
“…Low-fat diets with high sucrose content had the best effect in normalizing abnormal readouts (such as ketones), suggesting that this led to lesser reliance on fat as an energy source [ 41 ]. However, some discordant studies exist and have been discussed more extensively elsewhere [ 41 , 62 , 257 ]. An early small study looking at a low-fat/high carbohydrate diet claimed positive results [ 92 ], but concerns about its validity remain as this was ahead of genetic testing and the classification of patients was unclear.…”
Section: Nutritional Guidelines For Sma Patientsmentioning
confidence: 99%
“…Many studies have reported various forms of undernutrition and overnutrition in SMA patients, suggesting a multifactorial impairment that can produce different nutritional phenotypes [ 25 , 26 ]. For this reason, energy needs should be properly evaluated in each patient.…”
Section: Nutritional Aspects: Critical Issues and Possible Solutionsmentioning
confidence: 99%
“…Another interesting role of artificial nutrition in SMA1 has been explained by MC Ørngreen et al [ 42 ]. This study shows how in SMA1, as in all neurodegenerative diseases, a greater tendency to develop hypoglycemia during the fasting phases can be observed; the reason of this phenomenon seems to be to the lack of muscle mass as an important supplier of substrates for gluconeogenesis; therefore, due to the extremely reduced muscle mass, gluconeogenesis is less effective in these patients [ 26 ]. For this reason, an important role of artificial nutrition is to prevent prolonged fasting and, subsequently, hypoglycemia.…”
Section: Nutritional Aspects: Critical Issues and Possible Solutionsmentioning
confidence: 99%
See 2 more Smart Citations